Varieties of periphery and local agency in regional development. Issue 4 (3rd April 2023) - Nilsen, Trond; Grillitsch, Markus; Hauge, Atle
ABSTRACT: The extent to which structures and preconditions stimulate or hinder regional development is of interest in economic geography, as is the renewal of 'left-behind' peripheral regions. However, few studies have addressed how and to what extent peripheral regions differ. To disentangle the notion of peripheral regions as homogeneous and lacking knowledge sources, capital and networks, the paper discusses the characteristics of four types of peripheral regions: resilient regional service centres; locked-in specialized regions; vulnerable rural regions; and locked-in and vulnerable resource-based regions. By detailing the nuances of periphery, we systematize regions' challenges and opportunities and link these to local agency.